Application of refined nursing management in complete denture prosthodontics for elderly patients with low and flat alveolar ridge (精细化护理在牙槽嵴低平老年患者全口义齿修复中的作用) - TANG Youjia (汤有佳); YAN Tong (晏桐); CAI Wen (蔡文); SUN Yu (孙雨); LU Jinxin (卢金鑫) (Association of Integrative Nursing, 2022)
Objective To investigate the effect of refined nursing management in complete denture prosthodontics for elderly patients with low and flat alveolar ridge. Methods The clinical data of 44 elderly patients with low and flat alveolar ridge requiring complete denture prosthodontics were retrospectively analyzed. All patients received the refined nursing management after admission. The condition of denture restoration was evaluated. Results The dental restoration was not ideal in 17 patients wearing complete denture for the first time. The Satisfaction with return visit was 95. 45%(42/44) and 100. 00%(44/44) at 1 month and 3 months after discharge, respectively. Conclusion The effect of adopting refined nursing management for elderly patients with low alveolar ridge is very remarkable, with high satisfaction with nursing service mode and attitude, which has clinical promotion value. (目的 探讨精细化护理在牙槽嵴低平老年患者全口义齿修复中的应用效果。方法 回顾性分析44例牙槽嵴低平需要进行全口义齿修复的老年患者的临床资料, 患者入院后均开展精细化护理干预, 观察患者义齿修复情况。结果 44例患者中, 修复效果不佳者仅17例, 均为全口义齿初戴的患者。患者1、3个月复诊满意度分别为95. 45%(42/44)和100. 00%(44/44)。结论 精细化护理的应用有助于提高牙槽嵴低平老年患者全口义齿修复效果, 提升患者护理满意度。)